The Armed Goddess of the Achaeans at Incoronata (Metaponto) - Miller Ammerman, Rebecca (O T I V M, 2024)
The archaic figurine of a goddess brandishing a spear within the assemblage of votive terracottas recovered on the plateau of Incoronata in the territory of Metaponto invites comparison with similar statuettes of an armed female figure from other Greek settlements in southern Italy and Sicily. The terracotta figurines belong to extensive networks of related molds and casts, shared among coroplastic workshops not only at Metaponto but also between the Achaean city-states of Magna Graecia. Technical aspects of production, entwined with choices of iconography, reflect local cult practice and belief. Hera, Aphrodite, and Athena may all be characterized as warlike. The significance of these votive images of a goddess exhibiting a martial character is explored at each site before focusing on what the Metapontine terracottas of an armed goddess wearing a snake-trimmed aegis — which, as I argue, portray Athena Promachos — reveal about the cults practiced at San Biagio and Incoronata.